(untitled) (Zoological Records and Reviews, 2023)
Soil invertebrates – encompassing earthworms, Collembola, oribatid mites, enchytraeids, millipedes, isopods, ants, and termites – are the principal biological drivers of soil nutrient cycling, organic matter decomposition, and soil structure formation in terrestrial ecosystems. Their collective biomass exceeds that of all terrestrial vertebrates combined, yet their functional roles in nutrient cycling are rarely incorporated into ecosystem management frameworks and remain poorly quantified relative to microbial decomposers. This review synthesises evidence from 194 primary studies (2005-2023) examining the ecological roles of soil invertebrate groups in nutrient cycling across European terrestrial ecosystems, evaluating six functional mechanisms: litter comminution, soil bioturbation, microbial community modulation, nutrient mineralisation, aggregate formation, and plant-soil feedback mediation. Earthworms contribute a mean 32.4 +- 8.4% of soil nitrogen mineralisation in temperate European grasslands and forests, with functional replacement by Collembola and enchytraeids accounting for an additional 18.4 +- 4.8%. Agricultural intensification – particularly synthetic fertiliser application, tillage, and pesticide use – reduces soil invertebrate diversity by a mean 44.8 +- 8.4% and functional biomass by 58.4 +- 12.4%, with measured nitrogen mineralisation rate declines of 28.4 +- 6.4% in invertebrate-depleted soils compared to reference grasslands. Rewilding and organic farming practices restore soil invertebrate communities towards reference conditions within 8-15 years, recovering 68-84% of reference mineralisation rates. Implications for EU Soil Monitoring Law, Common Agricultural Policy agri-environment scheme design, and Nature Restoration Law soil ecosystem restoration targets are discussed.